Investigation of Aqueous and Non-Aqueous Phase Liquids Migration in Fractured Double-Porosity Soil - Loke Kok Foong; Norhan Abd Rahman (Institut Teknologi Sepuluh Nopember, 2017)
The issue of leakage from underground storage tank and spillage of contaminate liquids can contribute to the aqueous and non-aqueous phase liquids contamination into the groundwater, resulting in groundwater pollution and rendering the quality of groundwater unsafe for consumption. Ensuring availability and sustainable management of water and sanitation for all was the goal and target in the 2030 agenda for sustainable development, consisting of a plan of action for people, planet and prosperity of the United Nations. This paper is intended to investigate the aqueous and non-aqueous phase liquid migrations in the fractured double-porosity soil, which become important for sustainability of groundwater utilisation and a comprehensive understanding of the pattern and behaviour of liquid migration into the groundwater. For this aim, an experiment model was conducted to study the pattern and behaviour of aqueous and non-aqueous phase liquid migration in fractured double-porosity soil using digital image processing technique. Outcome of the experiments show that the fractured double-porosity soil has faster liquid migration at the cracked soil surface condition compared to intact soil surface. It can concluded that the factors that significantly influence the aqueous and non-aqueous phase liquids migration was the soil sample structure, soil sample fractured pattern, physical interaction bonding between the liquid and soil, and the fluid capillary pressure. This study demonstrates that the hue saturation intensity contour plot of liquids migration behaviour can provide detailed information to facilitate researchers and engineers to better understand and simulate the pattern of liquids migration characteristics that influence the groundwater resources.